2012
DOI: 10.1186/2008-2231-20-15
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of docetaxel surfaced Fe3O4 magnetite nanoparticles and their cytotoxicity on 4 T1 breast cancer cells

Abstract: BackgroundIn the recent years, there is an increasing attention to the using of Fe3O4 magnetite nanoparticles (MNPs) as drug delivery systems. Application of this nanoparticles could profit advantages of nanomedicine to enhance biological activity of pharmaceutical ingredients.MethodsFe3O4 MNPs were synthesised by a chemical method and characterized by transmission electron microscopy and energy-dispersive spectroscopy techniques. In the next step, docetaxel-coated Fe3O4 MNPs were prepared, using percipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…We observed that magnetite at concentrations above 100 mg/L induced a decrease in the percentage of viable cells, while at concentrations above 150 mg/L, magnetite treatments led to a pronounced LDH release in cultured human blood cells as compared to control values. Our results are in agreement with a previous study (Yazdi et al, 2012), which reported that magnetite NPs demonstrated strong cytotoxicity towards 4T1 breast cancer cells. The possible cytotoxic effects of magnetite have been reported by various researchers (Ding et al, 2010;Könczöl et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…We observed that magnetite at concentrations above 100 mg/L induced a decrease in the percentage of viable cells, while at concentrations above 150 mg/L, magnetite treatments led to a pronounced LDH release in cultured human blood cells as compared to control values. Our results are in agreement with a previous study (Yazdi et al, 2012), which reported that magnetite NPs demonstrated strong cytotoxicity towards 4T1 breast cancer cells. The possible cytotoxic effects of magnetite have been reported by various researchers (Ding et al, 2010;Könczöl et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…Recent studies suggest that multi-layer magnetic nanoparticle system(s) has been highly encouraged due to their theranostic (therapy and imaging/diagnosis) applications in cancer (Yallapu et al, 2013b; Yallapu et al, 2010a; Yallapu et al, 2012b; Yallapu et al, 2011). Yazdi et al (Yazdi et al, 2012) synthesized a magnetic nanoparticle loaded with docetaxel which showed higher cytotoxicity than the free drug in cancer cells and this delivery system can be used to inhibit development of resistance in cancer cells. This formulation has shown to be effective even at very low concentration levels.…”
Section: Using Nanotechnology To Overcome Docetaxel Resistancementioning
confidence: 99%